A Visual Comparative Study of Multi-Objective Transportation Problem in Several Approaches (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The main objective of this study was to present in one applet java program the five approaches for solving the Multi-Objective Transportation Problem (MOTP). The program was built using the java programming language, to solve the MOTP and to visualize the solution steps. In addition, the study made a comparision between the four different approaches used to solve the MOTP. For better understanding, the solution procedure is illustrated with a numerical example.